THE IMPLEMENTATION OF HOT SEAT TECHNIQUE AS A TEACHING TECHNIQUE TO TEACH SPOKEN DESCRIPTIVE TEXT TO THE SEVENTH GRADERS (RETAIN, 2013)
This study has aim to describe the implementation of “hot seat” technique in teaching speaking to the seventh graders, to describe e students’ speaking ability after the implementation of hot seat game as a teaching technique to teach spoken descriptive text to the seventh graders and present the students’ responses in implementation of hot seat game as a teaching technique to teach spoken descriptive text to the seventh graders. The researcher uses descriptive qualitative research without any statistical calculation. The result of this study showed hot seat technique could help the students to speak English more especially in describing an object. Hot seat could be applied in speaking class because this technique was effective to help students become effective in speaking English.Keywords : hot seat, speaking, descriptive text, seventh graders